Marketing for Non-marketers: Inclinations towards Market Orientation among Public University Librarians - Anis, Siti Nisrin Mohd; Hashim, Noor Hazarina; Rasli, Amran Md (International Review of Management and Marketing, 2016)
Marketing and market orientation are well–known subjects within the field of librarianship. Despite the nomological similarity between the terms, both are distinct in conceptualisation. Most librarians are actually referring to the total implementation of market orientation and cultural aspect of achieving patron's value when addressing libraries' marketing. In business studies, market orientation is a long established subject in itself. Yet, it hasn't been studied rigorously within the librarianship, though the librarians claim their understanding of the library's market and marketing. Nonetheless, the understanding about the difference is getting recognition among the librarians. Most studies will employ on either Narver and Slater's (1990) or Kohli and Jaworski's (1990) dimensions. However, researchers have argued that to explain the phenomena fully, it will mostly benefit when the subject is investigated as an integrated concept. This article would like to discuss the usefulness of employing market orientation within the public sector such as public university libraries and how the librarians may benefit from it. This article proposes market orientation as an important factor within the libraries' strategies, so that the librarians could perform better, remain competitive, continue to be relevant to their parents' organisations as well as an effort towards survival of the professions' itself. (202 words) Keywords: market orientation, public university librarians, strategic decision making, global changes JEL Classification: M31